2017
DOI: 10.3390/toxins9060189
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Enniatins and Beauvericin in Romanian Wheat Samples: From Raw Material to Products for Direct Human Consumption

Abstract: In this study, a total of 244 wheat and wheat-based products collected from Romania were analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS) in order to evaluate the presence of four enniatins (ENs; i.e., ENA, ENA1, ENB, and ENB1) and beauvericin (BEA). For the wheat samples, the influence of agricultural practices was assessed, whereas the results for the wheat-based products were used to calculate the estimated daily intake of emerging mycotoxins through wheat consumption for the Romanian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…In years to come efforts should be made to analyse also emerging Fusarium mycotoxins beauvericin and enniatins, which prevalence we have previously reported in wheat and maize originating from Poland and Hungary (as well as Nigeria and Zimbabwe) [67]. Also, other authors have confirmed the relevance of these emerging mycotoxins in Central and Eastern Europe [68]. These authors reported that enniatin B presented the highest incidence with 41% in wheat and 32% in wheat-based products and maximum levels of 815 μg kg −1 and 170 μg kg −1 in wheat and wheat-based products, respectively.…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 82%
“…In years to come efforts should be made to analyse also emerging Fusarium mycotoxins beauvericin and enniatins, which prevalence we have previously reported in wheat and maize originating from Poland and Hungary (as well as Nigeria and Zimbabwe) [67]. Also, other authors have confirmed the relevance of these emerging mycotoxins in Central and Eastern Europe [68]. These authors reported that enniatin B presented the highest incidence with 41% in wheat and 32% in wheat-based products and maximum levels of 815 μg kg −1 and 170 μg kg −1 in wheat and wheat-based products, respectively.…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 82%
“…A recent study conducted by Stanciu et al [ 33 ] did not quantify BEA in 40 pasta samples, while ENB was detected in 11% of the samples at average levels of 10.4 µg/kg and ENB in 9% of the samples at an average level 1.9 µg/kg.…”
Section: Discussionmentioning
confidence: 94%
“…There is a high occurrence of BEA in grains and wheat-based products like pasta, infant formulas, breakfast cereals, and biscuits, with incidences between 40 and 90% (Santini et al, 2012 ; Stanciu et al, 2017 ). In recent years, BEA has frequently been reported in different countries (South Africa, Norway, China, Croatia, Poland, Spain, Morocco…) as contaminants of, especially wheat, rye, oats, barley, and rice (Decleer et al, 2018 ).…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%